KONSTITUSIONALITAS HIRARKI PERATURAN DAERAH DALAM UNDANG-UNDANG NOMOR 12 TAHUN 2011 TENTANG PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN PERSPEKTIF TEORI HUKUM (Lex Jurnalica, 2019)
Abstract The regional regulations is a constitutional right of the regional authorities, whether provinces, regencies, and municipalities to carry out the autonomy and the duty of assistance as determination in The 1945 Constitution of The Republic of Indonesia in Article 18 point 6. Whereas Article 18 point 2 mentioned that the the regional authorities are arrange and organize theirselves the government affairs according to the principle of the autonomy and the duty of assistance. Due to the position of each type of the regional authorities is not constitutionally hierarchy, then the regional regulations as a legal product is also not hierarchy. However, The Act Number 12 of 2011 on The Establishment Regulation of Legislation to make hierarchy between provinces regulations that a higher level with the regulations of regencies and municipalities. It means that there has been